Autoimmune Cytopenias in Pediatric Hematopoietic Cell Transplant Patients - Neely, Jessica A.; Dvorak, Christopher C.; Pantell, Matthew S.; Melton, Alexis; Huang, James N.; Shimano, Kristin Ammon (Frontiers in Pediatrics, 2019)
Background: Autoimmune cytopenias (AICs) are potentially life-threatening complications following hematopoietic cell transplantation (HCT), yet little is understood about the mechanism by which they develop. We hypothesized that discordant B cell and T cell recovery is associated with AICs in transplant patients, and that this might differ based on transplant indication. Methods: In this case control study of children who underwent HCT at our institution, we evaluated the clinical and transplant characteristics of subjects who developed AICs compared to a control group matched by transplant indication and donor type. In cases, we analyzed the state of immune reconstitution, including B cell recovery, T cell recovery, and chimerism, immediately prior to AIC onset. Subjects were stratified by primary indication for transplant as malignancy (n=7), primary immune deficiency (PID, n=9) or other non-malignant disease (n=4). We then described the treatment and outcomes for 20 subjects who developed AICs. Results: In our cohort, cases were older than controls, were more likely to receive a myeloablative conditioning regimen and had a significantly lower prevalence of chronic GVHD. There were distinct differences in the state of immune recovery based on transplant indication. None of the patients (0/7) transplanted for primary malignancy had T cell recovery at AIC onset compared to 71% (5/7) of patients with PID and 33% (1/3) of patients with non-malignant disease. The subset of patients with PID and non-malignant disease who achieved T cell reconstitution (6/6) prior to AIC onset, all demonstrated mixed or split chimerism. Subjects with AIHA or Evans syndrome had particularly refractory courses with poor treatment response to IVIG, steroids, and rituximab. Conclusions: These results highlight the heterogeneity of AICs in this population and suggest that multiple mechanisms may contribute to the development of post-transplant AICs: patients with full donor chimerism have early B cell recovery without proper T cell regulation, while patients with mixed or split donor chimerism have residual host B or plasma cells making antibodies against donor blood cells. A prospective, multi-center trial is needed to develop personalized treatment approaches that target the immune dysregulation present and improve outcomes in patients with post-transplant AICs.